Accumulation over evolutionary time as a major cause of biodiversity hotspots in conifers. Issue 1912 (9th October 2019) - Sundaram, Mekala; Donoghue, Michael J.; Farjon, Aljos; Filer, Denis; Mathews, Sarah; Jetz, Walter; Leslie, Andrew B.
Abstract : Biodiversity hotspots are important for understanding how areas of high species richness form, but disentangling the processes that produce them is difficult. We combine geographical ranges, phylogenetic relationships and trait data for 606 conifer species in order to explore the mechanisms underlying richness hotspot formation. We identify eight richness hotspots that overlap known centres of plant endemism and diversity, and find that conifer richness hotspots occur in mountainous areas within broader regions of long-term climate stability. Conifer hotspots are not unique in their species composition, traits or phylogenetic structure; however, a large percentage of their species are not restricted to hotspots and they rarely show either a preponderance of new radiating lineages or old relictual lineages. We suggest that conifer hotspots have primarily formed as a result of lineages accumulating over evolutionary time scales in stable mountainous areas rather than through high origination, preferential retention of relictual lineages or radiation of species with unique traits, although such processes may contribute to nuanced differences among hotspots. Conifers suggest that a simple accumulation of regional diversity can generate high species richness without additional processes and that geography rather than biology may play a primary role in hotspot formation.